Preparation and characterisation of glass fibre/nanoclay/polypropylene nanocomposites / Nor Mas Mira binti Abd Rahman - Abd Rahman, Nor Mas Mira (2013)
Hybrid composites of glass fibre/nanoclay/polypropylene (PP) were prepared by extrusion and injection moulding. Fibre length distribution (FLD), Fourier-transform infra-red (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) together with characterisation of thermal, dynamic mechanical and mechanical properties were carried out on moulded specimens. FLD analyses revealed that composites with relatively high glass fibre loading exhibited low number average fibre length (Ln) and weight average fibre length (Lw) values than those containing relatively low glass fibre content. Due to the presence of added functional groups, a difference in the FTIR spectra for treated and untreated nanoclay powder was observed. XRD analyses showed that the interaction between nanoclay and PP matrix resulted in the intercalation of the polymer chains, which increased the nanoclay interlayer distance, as the TEM micrographs showed intercalated morphologies. Thermogravimetric analysis (TGA) revealed that the incorporation of untreated nanoclay into the glass fibre composite improved the thermal stability of the material. Further enhancement of this property was observed with the presence of treated nanoclay. Differential scanning calorimetric (DSC) study showed that the incorporation of untreated clay into glass fibre composite shifted the melting and crystallisation temperatures to higher values. Furthermore, the degree of crystallinity was strongly influenced by the presence of glass fibre and nanoclay in the matrix. Dynamic mechanical analysis (DMA) showed an increase in the storage modulus, indicating higher stiffness in case of the hybrid composites when compared to the clay nanocomposite, glass fibre composite and pure PP matrix. Glass fibre and nanoclay content showed a strong influence on the magnitude of tan δ. Incorporation of glass fibre into the PP matrix reduced the tensile strength of the binary composites, indicating a poor fibre-matrix interfacial adhesion. However, by introducing the untreated nanoclay in the glass fibre composite, the strength of the ternary hybrid composites increased. In addition, tensile modulus was enhanced with incorporation of glass fibre and further increased with an introduction of untreated nanoclay. On the other hand, the flexural modulus and strength were found to increase with glass fibre and nanoclay loadings. Further enhancement in tensile and flexural properties was observed with the presence of treated nanoclay. For glass fibre composite and clay nanocomposite, the peak load (P) and critical stress intensity factor (Kc) increased with filler contents. By contrast, the fracture energy (W) and critical strain energy release rate (Gc) decreased with the addition of nanoclay in the hybrid composites. Incorporation of maleic anhydride grafted polypropylene (MAPP) into the composites, led to improvement in the thermal and mechanical properties to various extents. In the hybrid composites, incorporation of 8 wt% MAPP provided the highest tensile and flexural properties (strength and modulus).